The impact of CBDC adoption on bank liquidity risk: evidence from the global banking sector - Nguyen, Dinh Trung; Nguyen, Minh Ngoc; Duong, Kim Thanh (Applied economics letters, 2025)
This article examines whether and how the adoption of CBDC influences bank liquidity risk. Using a sample of 804 listed commercial banks from 47 countries during the 2010-2021 period, we find that further stages of CBDC adoption subject banks to greater liquidity risk as indicated by higher bank financing gap ratio. The result still holds through a series of robustness checks, including when we employ bank liquidity creation measure to more comprehensively capture the level of bank liquidity, or when we use two-step system GMM to mitigate endogeneity concern. Further analyses show that this adverse impact of CBDC adoption on bank liquidity is driven by the reduction in banks' core deposits. Our results provide important policy implications for countries considering to implement a CBDC project.